1975
DOI: 10.7326/0003-4819-83-1-20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hematin in Hepatic Porphyria

Abstract: The present study was carried out in five cases of hepatic porphyria, including three of acute intermittent porphyria, one of variegate porphyria, and one of porphyria cutanea tarda in clinical remission. In two cases of acute intermittent porphyria (in relapse), a marked lowering effect on serum and urine porphobilinogen and delta-aminolevulinic acic was observed, together with prompt and gratifying clinical improvement. In a third case, in chemical remission but with longstanding psychoneurosis, no significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

1976
1976
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(37 citation statements)
references
References 27 publications
2
34
1
Order By: Relevance
“…Each infusion was followed by a highly significant decline of serum ALA and PBG. This was soon confirmed in several case studies (11)(12)(13)(14) reported from this laboratory, the decline being regularly associated with rapid clinical remission. Nevertheless, in porphyria roster no.…”
supporting
confidence: 58%
See 3 more Smart Citations
“…Each infusion was followed by a highly significant decline of serum ALA and PBG. This was soon confirmed in several case studies (11)(12)(13)(14) reported from this laboratory, the decline being regularly associated with rapid clinical remission. Nevertheless, in porphyria roster no.…”
supporting
confidence: 58%
“…The preparation of crystalline hemin and of the hematin solution (12) for infusion is to be described in detail elsewhere (1), also a recent, preferred manner of infusion. The latter is mentioned briefly in the following.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Substrate compensation for this defect is not possible, however, because the activity of URO-S becomes rate-limiting with consequent accumulation of PBG and ALA (22). Since hematin feedback inhibits ALA synthetase, infusions of this compound have recently been used to treat acute attacks of AIP with successful clinical remission (23). The elevated plasma levels of both ALA and PBG were shown to return (6).…”
Section: Discussionmentioning
confidence: 99%